Approaches to minimize overhang angles of SLM parts. Issue 2 (20th March 2017) - Cloots, Michael; Zumofen, Livia; Spierings, Adriaan Bernardus; Kirchheim, Andreas; Wegener, Konrad
Abstract : Purpose: For geometries exhibiting overhanging surfaces, support structures are needed to dissipate process heat and to minimize geometrical distortions attributed to internal stresses. The use of support structures is often time- and cost-consuming. For this reason, this study aims to propose an approach which minimizes the use of such structures. Design/methodology/approach: For minimizing the use of support structures, process parameters in combination with a contour-like exposure strategy are developed to realize support-less overhanging structures of less than 35°. These parameters are implemented in a shell-core strategy, which follows the idea of applying different processing strategies to the critical (overhanging) shell and the uncritical core of the part. Thereby, the core is processed with standard parameters, aiming a dense material. On the critical shell, optimized processing parameters are applied, reaching good results in terms of surface quality, especially at extreme overhang situations. Findings: The results show that the selective laser melting (SLM) technology is able to realize support-less overhanging surfaces by choosing suitable scan strategies and process parameters. Particularly good results are always obtained when the exposure direction of the shell is parallel to the contour of the sample. Originality/value: The validity of the results is demonstrated through the successful reproduction of the build strategy on two commercial SLM machines, reaching support-free builds of surfaces with an angle to the horizontal of less than or equal to 30°.